Food processing the spray drying of milk - Satterlee, Lowell D. (Penn Media Sales, 1992)
Explores the methods used by dairy plants to create powdered milk. Shows receipt of surplus milk at the plant and storage in silos, processing through separation and pasteurization, condensation, homogenization, the spray drying mechanisms, and packaging and transport.